HUBUNGAN PERSEPSI GURU TERHADAP KEPEMIMPINAN KEPALA SEKOLAH DENGAN KINERJA GURU TK DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Reza Triana; Wilson Wilson; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : Based on observations of the writer while in some kindergarten in the Kelurahan Simpang Baru Kecamatan Tampan found symptoms or phenomena include: The existence of some teachers who have not completed the learning tools, such as (RKH), assessment and so on, lack of initiative in developing a model teacher or learning methods are more appealing to children. Learning tends to be carried out by conventional methods, lack of creativity of teachers in the provision of media and learning resources that appeal to children. Presence of some rare rebuke the principal teacher when the teacher is not performing the task properly, existence of partial principals rarely directly involved in teaching and learning in schools. The purpose of this research was to determine the relationship between principal leadership with the kindergarten teacher's performance in the Kelurahan Simpang Baru Kecamatan Tampan Pekanbaru. The population in this study were all kindergarten teachers in Kelurahan Simpang Baru Kecamatan Tampan as many as 43 people comprising teachers from 12 kindergartens. The taking of sample with us random sampling technique are 43 people sampling. While for the purposes of the trial investigators determined 20 kindergarten teachers from the District Tampan. From the above results are known on the Kolmogorov-Smirnov column can be seen that the value of significance for teacher’s perceptions against principal leadership (0.063) and teacher performance (0.107), Based on the results of the homogenity test analysis, the value of statistical probability value of 0.683 and 0.191, and the resulting coefficient of determination is equal to r2 = 0.546 and p = 0.000 (p <0.05), it can be seen that the teacher perceptions of principal leadership for 54.6% effect on teacher performance, we conclude there is a relationship between teacher perceptions of principal leadership against the performance kindergarten teacher in Kelurahan Simpang Baru Kecamatan Tampan Pekanbaru. The level of the relationship between the two variables are ins a strong category. This means that the better the perception of teachers against the principal leadership performance kindergarten teacher in Kelurahan Simpang Baru Kecamatan Tampan Pekanbaru will also increase.Keywords: Principal Leadership, Teacher’s Performance